Rupture of an incisional hernia with evisceration of the gut: A case report - Edeh, Anthony J; Uchendu, Ugochukwu T; Nwangwu, Chukwuemeka I; Anekpo, Chijioke C; Aliozo, Chukwuebuka C (Indian Journal of Case Reports, 2018)
Spontaneous rupture of the abdominal wall hernia is very rare and usually occurs in incisional and recurrent groin hernias. Here, we report the case of rupture of a large incisional hernia with the evisceration of small bowel in a 56-year-old female. This surgical emergency was successfully managed using the current standard tension-free prosthetic mesh.